Optimizing the professionalism of the police work through education and training - Fadli Sudria Vera; Nizwardi Jalinus; Syahrial Bachtiar (Global Econedu, 2022)
Police brigadier education and training is a forum for creating human resources to acquire skills, knowledge and shape attitudes and behaviors related to the work to be carried out. Police brigadier education and training is very important for prospective police officers to carry out their duties professionally as members of the police, namely maintaining public security and order; enforce the law; and provide optimal protection, protection and service to the community.